PENCEGAHAN STUNTING MELALUI SOSIALISASI PROGRAM BAPAK ASUH ANAK STUNTING DI KABUPATEN SUBANG - Willya Achmad; Rizky Ilhami (Multidisiplin Pengabdian Kepada Masyarakat, 2022)
Stunting is a chronic nutritional problem that stunts children's physical growth and cognitive development, having a long-term impact on their future health and productivity. This study aims to investigate the effectiveness of the socialization of the Bapak Asuh Anak Stunting (BAAS) program in stunting prevention efforts in Subang Regency, Indonesia. This study utilized a qualitative design. Data was collected through a structured survey of mothers of children under five and fathers in Subang District. The results showed that the "Bapak Asuh Anak Stunting" (BAAS) program is an important initiative in stunting prevention in Indonesia. BAAS involves various stakeholders and focuses on families at risk of stunting, including stunted infants, pregnant women from at-risk families, brides-to-be, new families, and non-stunted toddlers from poor families. The program provides a package of benefits, including nutrition care and family economic support. Socialization of the BAAS program in Subang District through various methods, such as public campaigns, mass media, school education, community activities, and collaboration with the private sector, aims to increase community understanding and support for the program. Collaboration between the local government, the community, and the private sector is the key to success in implementing BAAS in stunting prevention efforts.